The Role of the Housekeeping Department in Supporting Cleanliness and Guest Satisfaction at PrimeBiz Hotel Kuta Bali - Lourdes, Evangelita Xavier De; Hadi, Syamsul (Mahesa Research Center, 2025)
This article aims to analyze the role of the Housekeeping Department in supporting cleanliness and guest satisfaction at PrimeBiz Hotel Kuta Bali. This study focuses on the influence of the quality of cleanliness managed by the Housekeeping Department on the level of guest satisfaction. Data were collected through two-month observations, in-depth interviews with 10 Housekeeping staff and hotel management, and a survey of 100 hotel guests selected using the purposive sampling method. Data were analyzed quantitatively using multiple regression analysis techniques to test the relationship between cleanliness quality and guest satisfaction. The results showed that cleanliness quality had a significant positive effect on guest satisfaction (? = 0.65, p < 0.01). Room cleanliness (? = 0.48) and public facilities (? = 0.37) were the main factors that influenced guest experiences at the hotel. Based on these findings, the study recommends that hotels improve cleanliness standards, implement a periodic cleanliness audit system, and use environmentally friendly cleaning products and technologies to create a more satisfying stay experience for guests.